Juridical Study of Police Members as Legal Advisors (JURNAL HUKUM SEHASEN, 2020)
The authority that the Police has is so great and broad in carrying out its duties as described in the author's description of the principles in carrying out its duties and functions, the authority of the police must comply with the principles in the Criminal Procedure Code, namely the principle of presumption of innocence, the principle of equality in advance. law, the right to provide legal assistance, every person suspected of committing a crime must be given the opportunity to receive legal assistance. non-compliance of financial service providers in supporting the anti-money laundering regime.